2020
DOI: 10.1590/0001-3765202020180230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-protein diet with different levels of amino acids on laying hen performance, quality and egg composition

Abstract: The present study aimed to investigate the consequences of dietary levels of crude protein (CP) and total sulfur amino acids (TSAA, Met+Cys) on productive performance, egg quality and egg components for Lohmann Brown laying hens through 18-34 weeks of age. A 2×3 factorial design experiment was conducted using two levels of CP (16 and 18 %) and three levels of Met+ Cys (0.67, 0.72 and 0.77 %). A total of 144 Lohmann Brown laying hens at 18 weeks of age were randomly divided into 6 treatment groups. The best val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…Inconsistent results stemming from dietary CP reductions on layer performance have been reported where some studies did not find impaired performance ( Liang et al., 2005 ; Gunawardana et al., 2008 ; Novak et al., 2008 ) while others reported underperformance in comparison to control diets ( Halle 2002 ; Valkonen et al., 2006 ; Alagawany et al., 2020 ). A lack of attention on protein digestive dynamics in reduced-crude protein layer diets which is important because they are supplemented with higher levels of nonbound amino acids has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results stemming from dietary CP reductions on layer performance have been reported where some studies did not find impaired performance ( Liang et al., 2005 ; Gunawardana et al., 2008 ; Novak et al., 2008 ) while others reported underperformance in comparison to control diets ( Halle 2002 ; Valkonen et al., 2006 ; Alagawany et al., 2020 ). A lack of attention on protein digestive dynamics in reduced-crude protein layer diets which is important because they are supplemented with higher levels of nonbound amino acids has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of poultry production is to achieve a desirable performance by considering the environmental issues related to intensive poultry operations (Rama Rao et al 2014;Rehman et al 2018). Since feed express the significant cost of production (Almeida et al 2019), poultry producers often interested in feeding diets with low nutrients level to reduce feed cost (Alagawany et al 2020), while it may not appear to supply sufficient energy and nutrients if birds could not adjust feed intake with diet dilution dePersio et al 2015;Alagawany et al 2020). It is critical to adjust the diet nutrient density to the actual feed intake of the bird to ensure sufficient consumption of nutrients (Leeson and Summers 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, Dowarah and Sethi (2014) reported that using different dietary CP levels during the periods (starter-23, 25, and 27%) and (finisher-18, 20, and 22%) had no effect on the growth performance of quails. A low protein diet supplemented with some amino acids improves the growth performance of quails, and it is a good strategy for reducing ammonia emissions and nutritional costs ( Alagawany et al, 2014 , 2016 , 2020 ; Attia et al, 2017 ). The use of synthetic or natural feed additives in diets containing low CP enhanced the feed conversion rate ( FCR ), growth, carcass traits, economic feasibility, and nitrogen retention of poultry ( Rehman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%